2022
DOI: 10.1371/journal.pone.0258828
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral economic methods to inform infectious disease response: Prevention, testing, and vaccination in the COVID-19 pandemic

Abstract: The role of human behavior to thwart transmission of infectious diseases like COVID-19 is evident. Psychological and behavioral science are key areas to understand decision-making processes underlying engagement in preventive health behaviors. Here we adapt well validated methods from behavioral economic discounting and demand frameworks to evaluate variables (e.g., delay, cost, probability) known to impact health behavior engagement. We examine the contribution of these mechanisms within a broader response cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 81 publications
(86 reference statements)
1
21
0
Order By: Relevance
“…In order to accurately measure the utilization of free testing, policymakers might want to understand how such delays affect the likelihood of accessing tests. Strickland et al ( 2022 ) asked participants the likelihood of accessing COVID-19 diagnostic tests when there was a delay to receiving the test or a delay to receiving the results. The price of the test ($125 or free) was also manipulated.…”
Section: Considering Time Costs In Policymentioning
confidence: 99%
See 2 more Smart Citations
“…In order to accurately measure the utilization of free testing, policymakers might want to understand how such delays affect the likelihood of accessing tests. Strickland et al ( 2022 ) asked participants the likelihood of accessing COVID-19 diagnostic tests when there was a delay to receiving the test or a delay to receiving the results. The price of the test ($125 or free) was also manipulated.…”
Section: Considering Time Costs In Policymentioning
confidence: 99%
“…If there is an additional delay, then there may be a risk that acceptance wanes. The COVID-19 pandemic stimulated useful behavioral economic studies of vaccine acceptance that can serve as a model for effective public health response to any future health crisis, be it an infectious disease or other environmental threat (Hursh et al, 2020 ; Strickland et al, 2022 ).…”
Section: Considering Time Costs In Policymentioning
confidence: 99%
See 1 more Smart Citation
“…The current results are in line with previous findings showing that steeper delay discounting is a key predictor of numerous health-related issues, including obesity, addictive behaviors, and anxiety and mood disorders 23 , many of which are exacerbated by pandemic conditions 25 , 26 . The extent to which delay discounting is a predictor of compliance with pandemic-mitigating behaviors other than vaccination (e.g., physical distancing, mask-wearing) is less clear 34 36 . Seemingly weak or contradictory findings may reflect the influence of confounding factors, such as psychological distress, which tends to be positively related to delay discounting 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of value using a demand curve perspective is hypothesized to separate distinct behavioral mechanisms-demand intensity and demand elasticity-characterizing allocation of behavior under differing conditions of constraint. Research using demand procedures has demonstrated their use in diverse areas of public health and policy by showing the concurrent and prognostic validity of demand indices in predicting substance use risk [6,7] and the sensitivity of demand procedures to experimental manipulations evaluating novel interventions [8] and simulating policy changes [9][10][11].…”
Section: Applications Of Behavioral Economic Demand In Addiction Sciencementioning
confidence: 99%